Formation of Mg–Nb–O rock salt structures in a series of mechanochemically activated MgH2 + nNb2O5 (n = 0.083–1.50) mixtures. (30th January 2016) - Pukazhselvan, D.; Bdikin, Igor; Perez, J.; Carbó-Argibay, Enrique; Antunes, I.; Stroppa, Daniel G.; Fagg, Duncan Paul
Abstract: The present study reports a comprehensive analysis regarding the formation of Mg–Nb combined active rock salt nanoparticles (Mgx Nby Ox+y ) in MgH2 /Nb2 O5 composite hydrogen storage system. This phase exhibit close crystallographic features to MgO and, hence was overlooked for years until recently. In order to explore the evolution of this phase in-situ in a MgH2 –Nb2 O5 hydrogen storage system, Nb2 O5 was mixed with MgH2 in various concentrations and the mechanochemical reaction products were monitored through 8 different compositions in three sets of reaction times, 1 h, 10 h and 30 h (totally 24 samples). Our study confirms the formation of rock salt type Mgx Nby Ox+y nanostructure over a wide compositional range in the MgH2 + nNb2 O5 (n = 0.083, 0.10, 0.123, 0.167, 0.25, 0.50, 1.0 and 1.5) system. In contrast to MgO, which is a well-known barrier layer in MgH2 system, the Nb dissolved MgO phases are shown to promote the hydrogen desorption performance of MgH2 . Graphical abstract: Highlights: Mechanochemical reaction was performed for 24 samples of MgH2 + n%Nb2 O5 . The value of n was varied between 0.083 and 1.5. Nb dissolved MgO phase with a typical formula of Mgx Nby Ox+y was observed. Mgx Nby Ox+y exhibit nearly identical structural features to MgO. Unlike MgO the Mgx Nby Ox+y is catalytically active.